Enhancing Mesenchymal Stem Cells (MSCs) for Therapeutic Purposes - Ylostalo, Joni H.; Durand, Nisha C. (2022)
The regenerative and immunomodulatory properties of mesenchymal stem cells (MSCs) have made these cells the focus of multiple pre-clinical studies and clinical trials. While the results from these clinical studies have established that MSCs are safe, the efficacy of these cells is not as well-established. In this regard, there have been increased efforts towards generating potentiated/activated MSCs with enhanced therapeutic efficacy. Research on the mechanisms for enhancing MSC potency and efficacy is an area of active study with great potential for translation into clinical settings. The purpose of this book is to bring together recent research from a broad range of topics relating to potentiation strategies for enhancing MSC therapeutic efficacy, including growth factor pre-conditioning, hypoxia, and 3D culture. The research compiled in this book increases the basic understanding of MSC culture techniques and describes some MSC preparations for potential novel therapeutic applications.